Content Commodification in the Digital Age : Implications and Challenges - Erri Kartika Purnama Putri; Zulaikha Zulaikha; Dhimam Abror; Nur Annafi Farni Syam Maella (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2024)
This research aims to explore the phenomenon of content commodification in the digital age, focusing on the economic, social, and cultural implications and challenges faced by content creators and digital platforms. Offers an original contribution to understanding how content commodification impacts various aspects of digital life. By highlighting key implications and challenges, it provides useful insights for content creators, platform managers, and policymakers. A qualitative approach was used in this research, involving in-depth interviews with content creators and policy analysis of digital platforms. Data was also obtained through a review of current literature from the last five years to support the research findings. Research limitations include limitations in sample size and diversity, time constraints, and participant and researcher bias. These limitations affect the generalizability of the results and highlight the need for further research with a wider scope and more diverse methods. The results show that content commodification provides significant economic opportunities for content creators, but also brings challenges such as income instability, copyright issues, and pressure to create viral content. Digital platform algorithms affect the visibility and sustainability of content. Social and cultural implications include changes in consumption patterns and social interactions, as well as cultural diversification influenced by platform algorithms. This research concludes that overcoming the challenges of content commodification requires diversifying sources of income, increasing copyright awareness, and developing fairer algorithms. Cooperation between creators, digital platforms, and policy makers is essential to create a more equitable and sustainable ecosystem in the creative industry and digital economy.